Combination of ICP-OES, XRF and XRD techniques for analysis of several dental ceramics and their identification using chemometrics. Issue 2 (2011) - Obeidat Obeidat, Safwan M. Safwan M.; Al-Momani Al-Momani, Idrees Idrees; Haddad Haddad, Asma'a Asma'a; Bani Yasein Bani Yasein, Motasem Motasem
Abstract : In this paper dental ceramic samples from seven vendors were studied. The elemental composition for each type was investigated using the ICP-OES and the XRF. Assessment of the seven types of ceramic was also successfully achieved using the XRD spectral data and processed with Principal Component Analysis (PCA). Detecting possible adulteration in different mass percentages of ceramic was also possible by applying the XRD data for the adulterated samples to the original PCA model.